Beyond biculturalism: the politics of an indigenous minority - O'Sullivan, Dominic (Huia, 2007)
"Beyond Biculturalism is a critical analysis of contemporary Maori public policy. Bicultural political theory dominated Maori/Crown relationships during the 1980s and 1990s and O'Sullivan argues that biculturalism inevitably makes Maori the junior partner in a colonial relationship that obstructs Maori aspirations to self-determination. The politics of indigeneity and self-determination are discussed as alternative political ideas for thinking about Maori relationships with the state. Against this background, and by drawing on Australian and Canadian comparisons, the book examines contemporary Maori political issues such as the Foreshore and Seabed Act 2004, Maori parliamentary representation, the 'one law for all' ideology, settlements of Maori grievances against the Crown, and Maori economic development."--BOOK JACKET.
Keywords: bicultural; crown policy; ethnic identity; government relations; iwi taketake; kāwanatanga; race relations; rangatiratanga; tāngata whenua

Faith, politics and reconciliation: Catholicism and the politics of indigeneity - O'Sullivan, Dominic (Huia, 2005)
Keywords: australia; christianity; iwi taketake; political activity; religion

Reconciliation as Public Theology: Christian Thought in Comparative Indigenous Politics - O’Sullivan, Dominic (International Journal of Public Theology, 2014)
Abstract Christian public theology extends reconciliation beyond its principal sacramental concern for relationships between God and penitent to the construction of ‘socially just’ public relationships for the settlement of intra-national conflict. In theological terms, reconciliation brings public relationships into what Hally calls ‘the Christ narrative of passion, death and resurrection’ in which the perpetrators of injustice repent and seek forgiveness. This article introduces the conflicts that these discourses aim to resolve in Australia, Fiji and New Zealand and explains and contrasts reconciliation’s relative importance in each of these jurisdictions. Moreover, the article’s cross-jurisdictional comparison shows reconciliation’s limits and possibilities as public theology, and argues that in Australia and New Zealand it has helped to create political environments willing to admit indigenous perspectives on a range of policy issues. On the contrary, however, the article also shows that the Fijian churches have distorted the concept of reconciliation to support political imperatives that are difficult to rationalize theologically, even though they are presented by the churches as being concerned with religious goals.
Keywords: christianity; colonisation; kāwanatanga; reconciliation; religion

Globalization and the Politics of Indigeneity - O'Sullivan, Dominic (Globalizations, 2012)
Indigenous peoples inevitably associate globalization with imperial expansion and the colonization of their territories. One associated scholarly view is that globalization's focus on capital accumulation sets aside indigenous cultural priorities to undermine self-determining authority over lands and resources (Fenelon and Hall, 2008; Friedman, 1999; Kelsey, 2005a, 2005b; Stewart-Harawira, 2005). Alternatively, globalization is an ambiguous paradox also providing significant benefits to indigenous peoples. In two very different Pacific countries, Fiji and New Zealand, the globalization of political and jurisprudential thought on the rights of indigeneity provides a significant counter to state assertions of absolute sovereignty. Globalization creates economic opportunities to reduce indigenous dependence on the state and in its contemporary expression is less significant than domestic factors in inhibiting indigenous aspirations. Inevitablemente, la población indígena asocia a la globalización con la expansión imperial y la colonización de sus territorios. Una visión académica asociada es que el enfoque de la globalización en la acumulación de capital, desestima las prioridades culturales indígenas para entorpecer la autoridad autodeterminante sobre la tierra y los recursos. (Fenelon and Hall, 2008; Friedman, 1999; Kelsey, 2005a; 2005b; Stewart-Harawira, 2005). Por otro lado, la globalización es una paradoja ambigua que también provee beneficios a las poblaciones indígenas. En dos países diferentes del Pacífico, Fiyi y Nueva Zelanda, la globalización del pensamiento político o jurisprudencial sobre los derechos del indigenismo, provee una lucha importante contra las afirmaciones estatales de una soberanía absoluta. La globalización crea oportunidades económicas para reducir la dependencia indígena del estado y su expresión contemporánea es menos importante que los factores domésticos que inhiben las aspiraciones indígenas. 伴随着帝国的扩张和其领土的被殖民化，土著居民无可避免地被卷入全球化中。一种相关学术观点认为，全球化对资本积累的关注不顾土著民的文化优先权，损害了土著民对土地和资源的自决权力。（Fenelon 和 Hall, 2008; Friedman, 1999; Kelsey, 2005a; 2005b; Stewart-Harawira, 2005）另一种观点认为，全球化是一种不确定的悖论, 也为土著民带来了巨大利益。在两个截然不同的太平洋国家———斐济和新西兰，关于土著民权利的政治和法律思考的全球化对国家声称的绝对主权提出了挑战。全球化为土著民减少对国家的依赖创造了经济机遇；而且在抑制土著民的权利主张方面，其当今表现作用不及国内因素显著。 원주민들은 불가피하게 세계화를 제국주의적 팽창과 영토의 식민화와 연계시킨다. 관련된 학술적 견해는 자본축적에 초점을 맞춘 세계화가 토지와 자원에 대해서 자결 권위를 약화시키 위하여 원주민들이 문화적으로 우선시 하는 사항을 제켜 놓는다는 것이다 (Fenelon and Hall, 2008; Friedman, 1999; Kelsey, 2005a; 2005b; Stewart-Harawira, 2005). 대안적으로 세계화는 원주민들에게 상당한 이익을 가져다 주는 애모보호한 패러독스이다. 서로 다른 두 태평양 국가인 피지와 뉴질란드에서 원주민의 권리에 대한 정치적, 법률적 사유의 세계화는 절대적 주권을 주장하는 것에 대한 중요한 반론을 제공한다. 세계화는 국가에 의존하는 원주민들의 종속성을 약화시키는 경제적인 기회를 만들고 또한 현대적인 표현으로 내생적인 갈망을 금지시키는데 국내적인 요인들보다 덜 중요하다.
Keywords: globalisation; government; rangatiratanga; sovereignty

Reconciliation: The Political Theological Nexus in Australasian Indigenous Public Policy - O’Sullivan, Dominic (International Journal of Public Theology, 2010)
Reconciliation brings together Christological and anthropological dimensions of human thought to illustrate the nexus between religious principles and political means. For the state reconciliation is concerned with social cohesion and political stability. For the church, it extends the sacramental notion of reconciliation between God and penitent to public relationships. This article examines Roman Catholic contributions to secular reconciliation debates. It shows how religious precepts create moral imperatives to engagement with secular discourses as a necessary element of Christian mission. It also argues that the church’s role in the disruption of indigenous societies creates an additional moral imperative to engage in reconciliation as mission and to articulate a Christian vision of indigenous rights.
Keywords: christianity; kāwanatanga; open access version available; reconciliation; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty settlements

Needs, Rights and "One Law for All": Contemporary Debates in New Zealand Maori Politics - O'Sullivan, Dominic (Canadian Journal of Political Science / Revue canadienne de science politique, 2008)
This paper examines contemporary debates in Maori politics by responding to the argument of the former leader of the opposition National party, Don Brash, that Maori public policy is most properly based on "need" alone because indigenous status offers no "rights" beyond those of common national citizenship. The paper's alternative argument is that the politics of indigeneity and associated theories of self-determination provide a way of avoiding a general belief that addressing need is all that is required to include Maori fairly in the national polity. It is argued that Maori ought to enjoy rights of indigeneity as the basis of an inclusive, cohesive and fair society. /// Cette étude examine certains débats dans le domaine de la politique maorie en répondant aux propos de l'ancien chef du parti National, Don Brash, selon qui la politique publique maorie se baserait le plus aptement sur la notion du seul 'besoin', le statut de peuple indigène ne conférant aucun 'droit' au-delà de ceux qu'accorde la citoyennenté nationale régulière. Nous proposons par contre que la politique de l'indigénéité et les théories de l'auto-détermination qui y sont associées constituent un moyen de parer à une croyance généralisée qu'il suffirait de suppléer au besoin pour inclure avec justice les Maoris dans la politique nationale. Nous démontrerons que dans une société inclusive, cohésive et juste, les Maoris devraient jouir des droits accordés par l'indigénéité.
Keywords: māori rights; protest; racism; ōrewa speech

The Treaty of Waitangi in Contemporary New Zealand Politics - O'Sullivan, Dominic (Australian Journal of Political Science, 2008)
This paper identifies three discourses that are prominent in contemporary Treaty of Waitangi policy debate, each with significantly different implications for Maori political status within the modern nation-state. At one extreme the Treaty's significance is exaggerated by overemphasis on partnership as an implicit Treaty principle. At another extreme the Treaty's significance is understated by an assimilationist position that denies the Treaty's relevance to Indigenous rights which, in turn, imposes serious constraint on the extent to which partnership can actually develop into comprehensive policy practice. An alternative position is one that sees the Treaty, which is supported in international law, as affirming a twofold conception of citizenship as the basis of both individual and collective Maori rights.
Keywords: māori rights; partnership; tiriti o waitangi/treaty of waitangi; treaty obligations

Needs, rights, nationhood, and the politics of indigeneity - O’Sullivan, Dominic (MAI review, 2006)
In 2004 the appointment of a Coordinating Minister Race Relations, signalled a shift in elite Māori policy thinking from a long-standing cautious bipartisan acceptance of selfdetermination towards a re-emergent assimilationist ‘one law’ for all discourse. The question simplistically posed by the Leader of the Opposition was should welfare entitlements be granted on the basis of need or race (Brash 2004)? Beneath this question lies an ideological assumption which privileges assimilation over indigeneity as the basis of Māori participation in public affairs. This paper therefore asks: are Māori peoples with rights, or individuals with needs? Is there a deeper politics of indigeneity providing a legitimate foundation for rights which are not necessarily superior to the rights of citizenship, but are important and distinguishable adjuncts? These questions transcend the issue of welfare entitlements to wider questions about the nature and terms of Māori belonging to the liberal polity. The paper highlights the political tension between government attempts to remove indigeneity from the public agenda in response to populist pressure and a pragmatic acceptance that New Zealand ‘needs’ Māori to increase their contribution to the national economy and that the realisation of this goal may in fact depend on the fuller citizenship imagined by the politics of indigeneity.
Keywords: assimilation; indigenous rights; māori rights; rangatiratanga; self-determination

Māori education and principles of self-determination in the twenty-first century. - O’Sullivan, Dominic (Waikato Journal of Education, 2001)
This paper argues that self-determination to the greatest extent possible is a legitimate aspiration for Maori people. It is argued that in education this requires a philosophical and policy response more focused on Maori autonomy than can be provided within the bicultural framework that has lately informed Maori relationships with other actors in the education arena. The paper considers the place of kohanga reo, kura kaupapa Maori and wananga in relation to broader Maori aspirations for self-determination and discusses proposals that these aspirations be furthered through the establishment of a Maori Education Authority. It is also argued that opportunities for self-determination in New Zealand are compromised by the government's unwillingness to alter a tightly controlled centralised education market to provide genuine Māori autonomy over what type of education might be available and to what end.
Keywords: crown policy; education; rangatiratanga; self-determination

Covenants, Treaties and the Politics of Reconciliation - O'Sullivan, Dominic (Uniting Church Studies, 2010)

The crisis of policy failure or the moral crisis of an idea: colonial politics in contemporary Australia and New Zealand - O’Sullivan, Dominic (Political Science, 2022)
When analysing Indigenous public policy, crisis is best seen as the moral crisis of an enduring idea rather than the crisis of sporadic and unconnected instances of policy failure. In Australia and New Zealand, states use manufactured crises of Indigenous personal deficiencies to justify colonial authority. A justification which may be countered by positioning colonialism itself as the point of crisis. From this perspective, the crisis in Indigenous public policy is not resolved by the state becoming better at policy-making or more attentive to the egalitarian distribution of public resources. Instead, it is in the non-colonial possibilities of Indigenous self-determination that paths beyond crisis may lie. In practical terms, by ensuring spaces of independent Indigenous authority alongside spaces of distinctive culturally framed participation in the public life of the state. The potential for such arrangements in Australia is discussed with reference to a proposed First Nations’ Voice to Parliament and possible treaties between First Nations and the state. For New Zealand, their potential is discussed with reference to te Tiriti o Waitangi’s affirmation of independent Māori authority (rangatiratanga) and substantive state citizenship.
Keywords: Aboriginal Australians; Authority; Citizenship; Colonialism; Crises; Crisis theory; Egalitarianism; Indigenous peoples; Justification; Legislatures; Maoris; Policy making; Positioning; Public life; Public policy; Self determination; State; Treaties; colonialism; indigenous politics; indigenous self-determination; māori politics; political crisis; treaty of waitangi

The Politics of Indigeneity and contemporary challenges to Maori self-determination - O'Sullivan, Dominic (The Australian Missiology Conference, 2004)
Keywords: Populist; Self-Determination; Treaty of Waitangi

Māori Self-Determination: In the Modern Political Context - O'Sullivan, Dominic (AlterNative: An International Journal of Indigenous Peoples, 2005)
Keywords: Commonwealth; Democracy; Political Parties; Te Tiriti o Waitangi

Maori Public Policy: Needs rights and the Politics of Indigeneity - O'Sullivan, Dominic (APSA, 2007)
In 2004 the appointment of a Coordinating Minister Race Relations, signalled a shift in elite Maori policy thinking from a long-standing cautious bipartisan acceptance of self-determination towards a re-emergent assimilationist 'one law' for all discourse. The question simplistically posed by the Leader of the Opposition was should welfare entitlements be granted on the basis of need or race? (Brash 2004). Beneath this question lies an ideological assumption which privileges assimilation over indigeneity as the basis of Maori participation in public affairs. This paper therefore asks: are Maori peoples with rights, or individuals with needs? Is there a deeper politics of indigeneity providing a legitimate foundation for rights which are not necessarily superior to the rights of citizenship, but are important and distinguishable adjuncts? These questions transcend the issue of welfare entitlements to wider questions about the nature and terms of Maori belonging to the liberal polity. The paper highlights the political tension between government attempts to remove indigeneity from the public agenda in response to populist pressure and a pragmatic acceptance that New Zealand 'needs' Maori to increase their contribution to the national economy and that the realisation of this goal may in fact depend on the fuller citizenship imagined by the politics of indigeneity.
Keywords: Maori Politics; New Zealand Politics

Indigeneity, Ethnicity, and the State: Australia, Fiji, and New Zealand - O’Sullivan, Dominic (Nationalism and Ethnic Politics, 2014)
This article draws on the politics of indigeneity to distinguish the claims of first occupancy from simple ethnic identity politics, illustrating that relative political marginalization in Australasia is not so much a function of minority status but of indigeneity itself. The politics of indigeneity's aim is to create political space for self-determination and a particular indigenous share in the sovereign authority of the nation-state itself. The Australasian states are compared with Fiji to demonstrate that the significance of historical constraints on political authority transcend the withdrawal of a colonial power and the restoration of collective indigenous majority population status.

Maori Self-Determination: Towards Differentiated Liberal Citizenship - O'Sullivan, Dominic (Australian Journal of Politics & History, 2019)
During the 1980s and 1990s biculturalism was the ascendant political philosophy for managing the relationship between the New Zealand Crown and the indigenous Maori population. Biculturalism understood Maori politics as a partnership between Maori and the state, grounded in the Treaty of Waitangi, the agreement signed in 1840 from which British government was established. Biculturalism was presented as morally superior to multiculturalism which was understood as setting aside Maori Treaty rights and rights of prior occupancy in favour of less substantive rights available to Maori as one of many ethnic minorities. However, a deeper reading of multicultural political theory provides an instructive critique of biculturalism's inherent limits from the perspective of the Maori right to self-determination. It shows why biculturalism's influence waned. It also shows why Matike Mai o Aotearoa, a blueprint for constitutional transformation commissioned by tribal leaders is unlikely to succeed as a contemporary attempt to reassert biculturalism's influence. Multicultural theory is not a panacea for the right to self-determination, but it does not restrict the development of a broader Maori-centred differentiated liberal citizenship in the ways that biculturalism precludes.
Keywords: Biculturalism; Multicultural; Politics; Self-Determination

Te Tiriti o Waitangi—neither “one people” nor partners: rangatiratanga and inclusive democratic kāwanatanga - O’Sullivan, Dominic (AlterNative: An International Journal of Indigenous Peoples, 2024)
Te Pati Māori (The Māori Party) proposes removing the British monarch as head of state so that Te Tiriti o Waitangi’s (the Māori text of the Treaty of Waitangi) (Te Tiriti) promise of fulfilling partnership may be realized. The ACT (Association of Consumers and Taxpayers) Party’s alternative argument is that partnership is among a body of treaty principles that give Māori people (Indigenous peoples of New Zealand) political advantage over others. These alternative perspectives transcend time because neither partnership nor equality as the ACT party presents it meets the possibilities of liberal democratic citizenship that may be read into Te Tiriti. Instead, equality is enhanced by interpreting Te Tiriti as constituting a commonwealth with hapū (sub-tribes) as existing political communities, and kāwanatanga (government) as a new one, with powers and responsibilities grounded in equal tikanga (cultural practices and proper conduct). The powers of government may then be shared, through participatory parity.

The Politics of Indigenous Exclusion in Australia and New Zealand - O’Sullivan, Dominic (Current History, 2024)
In both Australia and New Zealand, Indigenous peoples have called for alternative non-colonial political arrangements. In October 2023, Australians voted in a referendum against distinctive Indigenous participation in public policymaking, which had been proposed as a step toward a more inclusive political system. On the same day, New Zealand elected a new Parliament, leading to the formation of a government comprising three parties that had campaigned against what they saw as excessive Māori political influence. Comparing these developments and the histories of the two countries raises questions about liberal equality, democratic citizenship, and whether all or just some citizens should own the liberal democratic state.

Indigeneity: a politics of potential: Australia, Fiji and New Zealand - O'Sullivan, Dominic (Policy Press, 2017)
Keywords: australia; citizenship; government; kāwanatanga; rangatiratanga

Maori self-determination and a liberal theory of indigeneity - O'Sullivan, Dominic (Restoring Indigenous Self-Determination: Theoretical and Practical Approaches, 2014)
Indigenous peoples find themselves locked in power struggles with states and transnational actors who resist their claims, raising important questions in theory and practice. Edited by Marc Woons.
Keywords: rangatiratanga; self-determination; sovereignty

Indigenous Participation in Elective Bodies: The Maori in New Zealand - O'Sullivan, Dominic; Xanthaki, Alexandra (International Journal on Minority and Group Rights, 2009)
The article argues that Maori political participation in New Zealand constitutes a positive example of how the current international standards on indigenous political participation can be implemented at the national level. Notwithstanding the weaknesses of the system and the challenges laying ahead, the combination of the Mixed Member Proportional electoral system, dedicated Maori seats and the establishment of the Maori Party have ensured a Maori voice in Parliament and have broadened the possibilities of effective indigenous participation in the political life of the state. Such state practice that implements the 2007 UN Declaration on the Rights of Indigenous Peoples firmly confirms the position of the Declaration within current international law.
Keywords: UNDRIP; elections; electorates; government; indigenous rights; mmp electoral system; political participation; te pāti māori

Philosophical Foundations of Maori-Crown Relations in the Twenty First Century: Biculturalism or Self-Determination - O'Sullivan, Dominic (APSA, 2003)
This paper demonstrates that the philosophical premises underlying biculturalism and self-determination lead to different conclusions about where power properly resides with respect to Crown/Maori relations in New Zealand. It is argued that biculturalism is not the panacea for the realisation of legitimate Maori aspirations that has been assumed by both Maori and Pakeha policy elites over the past twenty years because it makes assumptions about power relationships which limit greater degrees of Maori autonomy ' one step towards self-determination is permitted, but the next prevented. Biculturalism can not realise greater autonomy because it is concerned primarily with relationships among people in institutional settings and within and among bureaucratic institutions. Therefore it is less likely to meet Maori aspirations than self-determination which is concerned with creating, to the greatest extent possible, independence and autonomy for groups, not necessarily in isolation from wider society, but certainly apart from controls and regulations imposed from outside the would be self-determining community. Self-determination locates power, at least to some extent, within traditional Maori social units, while biculturalism, although assuming a sharing of power, inevitably gives Maori the status of junior partner in a project designed to modify state institutions to make them more responsive to Maori interests. While in itself this is advantageous to Maori, biculturalism is not a substitute for the affirmation of traditional social structures as the central point in a Maori quest for greater independence from an historically intrusive state.
Keywords: Biculturalism; Indigenous Politics; Maori; New Zealand Politics; Self-Determination

Post Colonialism - O'Sullivan, Dominic (New Zealand Government and Politics, 2015)
Keywords: New Zealand-Politics and government-1972-

Scaling up education reform: addressing the politics of disparity - Bishop, Russell (NZCER Press, 2010)
Keywords: education; educational change; mātauranga māori

The Waitangi Tribunal’s WAI 2575 Report - O’Sullivan, Dominic; Came, Heather; Kidd, Jacquie; McCreanor, Timothy (Health and Human Rights, 2020)
Te Tiriti o Waitangi, a treaty negotiated between Māori (the Indigenous peoples of Aotearoa) and the British Crown, affirmed Māori sovereignty and guaranteed the protection of hauora (health). The Waitangi Tribunal, established in 1975 to investigate alleged breaches of the agreement, released a major report in 2019 (registered as WAI 2575) about breaches of te Tiriti within the health sector in relation to primary care, legislation, and health policy. This article explores the implications of this report for the New Zealand health sector and the decolonial transformation of health systems. The tribunal found that the Crown has systematically contravened obligations under te Tiriti across the health sector. We complement the tribunal’s findings, through critical analysis, to make five substantive recommendations: (1) the adoption of Tiriti-compliant legislation and policy; (2) recognition of extant Māori political authority (tino rangatiratanga); (3) strengthening of accountability mechanisms; (4) investment in Māori health; and (5) embedding equity and anti-racism within the health sector. These recommendations are critical for upholding te Tiriti obligations. We see these requirements as making significant contributions to decolonizing health systems and policy in Aotearoa and thereby contributing to aspirations for health equity as a transformative concept.

Critical Tiriti Analysis: A prospective policy making tool from Aotearoa New Zealand - O’Sullivan, Dominic; Came, Heather; Kidd, Jacquie; McCreanor, Tim (Ethnicities, 2023)
Restrictions on Indigenous peoples’ contributions to policymaking pervade post-settler societies like Australia, Canada and Aotearoa. Such effects are observed in spite of agreements like Te Tiriti o Waitangi in Aotearoa and the United Nations’ Declaration on the Rights of Indigenous Peoples. Te Tiriti, negotiated between the British Crown and Māori (Indigenous peoples of Aotearoa), may have been entered into honourably by both parties, but the Crown has consistently resisted its implementation. Contemporary colonialism is characterised by the entrenched and on-going displacement of Indigenous people’s authority by settler states, rationalised by race as a determinant of human worth. Impacts include land alienation, unsustainable resource exploitation and marginalising Indigenous voices from opportunities to make policy consistent with Indigenous values and preferred ways of living. Colonialism normalises institutional racism so that public policy outcomes are persistently unjust. This article describes Critical Tiriti Analysis (CTA), an original contribution to transforming colonial policy, which retrospectively evaluates whether any specific policy document is consistent with Te Tiriti. Substantial interest in CTA from policymakers, practitioners, and scholars led to the development of the tool as a prospective guide to making policy that is consistent with authoritative interpretations of Te Tiriti, and therefore, more likely effective in producing public policies which eliminate inequities. CTA was initially focused on health policy and built on a series of questions that arise from our interpretations of the text of Te Tiriti, contemporary Tiriti scholarship and jurisprudence, and our observations of the ways in which the method is being used by ourselves and others. Although deeply grounded in Aotearoa, we argue that CTA may be transferable to other colonial contexts, such as the Australian where treaties between First Nations and the state are being contemplated, and Canada which has passed legislation to implement the Declaration on the Rights of Indigenous Peoples.
Keywords: Public Policy; Te Tiriti o Waitangi

A critical review of the Cabinet Circular on Te Tiriti o Waitangi and the Treaty of Waitangi advice to ministers - O’Sullivan, Dominic; Came, Heather; McCreanor, Tim; Kidd, Jacquie (Ethnicities, 2021)
The New Zealand state developed from a treaty between the British Crown and hapū (sub-tribes) in 1840. The te Reo (Māori language) text and the English version of the agreement are fundamentally different. Breaches of this treaty and tension over how the political relationship between Māori and the Crown should proceed are ongoing. In 2019, the Cabinet Office issued a Circular instructing bureaucratic advisers of the questions they should address when providing advice to ministers on the agreement’s contemporary application. In this article, we use Critical Tiriti Analysis (CTA) – an analytical framework applied to public policies – to suggest additional and alternative questions to inform bureaucratic advice. The article defines CTA in detail and shows how using it in this way could protect Māori rights to tino rangatiratanga (a sovereignty and authority that is not subservient to others) and substantive engagement, as citizens, in the formation of public policy. This article’s central argument is that the Circular reflects an important evolution in government policy thought. However, in showing how the Circular privileges the English version (the Treaty of Waitangi) over the Māori text (Te Tiriti o Waitangi), the article demonstrates how Māori political authority remains subservient to the Crown in ways that Te Tiriti did not intend. We show through the conceptual illustration of the care and protection of Māori children, despite the significant evolution in government thought that it represents, these rights are not fully protected by the Circular. This is significant because it was Te Tiriti, with its protection of extant Māori authority and sovereignty, that was signed by all but 39 of the more than 500 chiefs who agreed to the British Crown establishing government over their own people, but who did not agree to the colonial relationship which may be read into the English version.
Keywords: Cabinet; Critical Tiriti Analysis; Public Policy; Self-Determintation; Te Tiriti o Waitangi; Treaty of Waitangi

The Importance of Political Theory - O'Sullivan, Dominic (Government and politics in Aotearoa New Zealand, 2021)
Keywords: Elections -- New Zealand; Māori (New Zealand people) -- Politics and government; New Zealand -- Foreign relations; New Zealand -- Politics and government; Political parties -- New Zealand; Proportional representation -- New Zealand; Representative government and representation -- New Zealand; Tōrangapū

Critical policy Analysis - O'Sullivan, Dominic; Came, Heather (Encyclopedia of Health Research in the Social Sciences, 2023)
Critical policy analysis (CPA) is a technique concerned with how the location of power within the policy system influences social outcomes. CPA shows how and why it is unreasonable to assume that policy making is a politically neutral, objective, and simple technical process. This entry illustrates critical policy analysis through the example of colonial health policy in New Zealand. Institutional racism is often normalised within colonial settings and CPA can respond with a range of tools to privilege Indigenous values and contexts in policy development and implementation. Critical Tiriti Analysis is an emerging CPA method of policy analysis. It emphasises making policy transparently, with substantive Māori (Indigenous peoples of New Zealand) leadership. It is becoming increasingly influential among policy makers in New Zealand with the potential to counter racism as a modifiable determinant of health, for example.
Keywords: Public Policy; Te Tiriti o Waitangi

The politics of reconciliation in Australia and New Zealand - O’Sullivan, Dominic (Injustice, Memory and Faith in Human Rights, 2017)
This chapter draws on New Zealand examples to contextualize its assessment of reconciliation as public memory in Australian policy discourse. The Treaty of Waitangi has provided the rationale and framework for successive New Zealand governments to say sorry for acts of aggression against Maori tribes. In New Zealand, sorrow is expressed through Acts of Parliament that serve not only as instruments of restitution but as symbols of public memory. Faith and memory are similarly important to wider Christian treaty discourses, as it was Anglican missionaries who drafted the agreement and translated it from English to Maori. The Pastoral letter is drawn into Catholic public memory to justify the development of a public theology of reconciliation. Self-determination belongs first and foremost to individuals, but in Catholic teaching the human person is fundamentally social and exercises the rights and responsibilities of their human being in association with others.
Keywords: reconciliation; religion